A Systematic Review of Integrating UTAUT2, Technology Readiness and Value Belief Norm Models in Explaining Pro-Environmental Behavior - Nani Irma Susanti; Jati Waskito; K Kussudyarsana (Universitas Muhammadiyah Surakarta, 2025)
This paper presents a systematic literature review exploring the integration of the UTAUT2 model, Technology Readiness (TR), and Value–Belief–Norm (VBN) in the study of pro-environmental behavior. The review synthesizes existing research published between 2015 and 2025 to identify key factors influencing pro-environmental behavior through the integration of these models. A quantitative methodology was predominantly employed, with a focus on consumer technology adoption, psychological readiness, and environmental values. Results highlight the synergistic influence of these models, with UTAUT2 addressing technology adoption, TR measuring individual readiness, and VBN emphasizing moral and value-based motivations. The paper contributes to theoretical understanding by integrating these models to explain sustainable behavior, offering implications for policy and practical applications in environmental technology adoption. Research gaps identified include the need for further exploration of these models in developing countries and across diverse green technologies.